Pričakovanja najemnikov v povezavi s programom "strankina izbira" - Zijlstra, Sake (Urbani izziv, 2009)
In the Netherlands, several housing associations have started offering a substantial part of their housing reserve with a purchase option. This allows tenants from either new or existing dwellings to choose between entering into a standard tenancy contract and purchasing the dwelling. Housing experts expect many positive effects of what is referred to as 'Client's Choice' programmes, but many of the effects have not been evaluated. In this article, we evaluate several effects based on the tenants' opinions gathered through the use of interviews. The tenants appreciate the offer but their expectations of and experiences with the Client's Choice programme differ from those of the management of housing associations and are generally less optimistic.
Keywords: etažna lastnina; najem; nakup; Nizozemska; stanovanja; stanovanjska naselja; stanovanjska politika; stanovanjska pravica; večstanovanjske zgradbe